Desain Pembangkit Listrik Tenaga Surya (PLTS) Off Grid Dusun I Negeri Hutumuri: Studi kasus di Negeri Hutumuri, Kecamatan Leitimur Selatan, Kota Ambon - Matakena, Chelsya; Parera, Lory Marcus; Jamlaay, Marselin (JURNAL SIMETRIK, 2025)
This research aims to design an Off-Grid Solar Power Plant (PLTS) in Dusun I Negeri Hutumuri, to overcome the limited electricity supply from PLN, which often experiences periodic blackouts. Off-Grid PLTS was chosen as an alternative solution because it uses abundant solar energy in the region, is environmentally friendly, and does not depend on conventional power grids. This research begins with an analysis of the daily load requirements in Dusun I Negeri Hutumuri, which include household needs, public facilities such as schools and health centers, with total energy consumption reaching 605.064 kWh. In the design of this Off-Grid PLTS system, the main components used include solar modules, batteries, and inverters. The peak capacity required for this solar system is 172 kWp with a total energy of 168,073 Wh. Based on the calculation results, this system uses 210 solar modules connected in a series-parallel configuration, as well as five inverters with a capacity of 20 kW each. Keywords: PLTS Off-Grid, DOD, MPPT